Luxe, vanité, luxure : quelques considérations sur les paradoxes des lois somptuaires concernant la garde-robe féminine en Italie, de la fin du Moyen Âge à la première partie de l’ère moderne - Del Mastro, Diana (Renaissance and reformation, 2023)
In the sixteenth century, sumptuary laws regulated not only the use of garments and personal adornments but also extended to banquets, marriages, baptisms, and funerals, in order to guarantee the traditional values of austerity and decorum. Established authorities were therefore anxious on two counts, almost antithetically opposed: on the one hand they were concerned about the circulation of money, on the other about potential contamination between social groups. By investing clothing with a symbolic value, the regulation of permissible attire could also be used to help distinguish and identify marginalized groups, such as Jewish women and prostitutes. The proliferation of women’s resistance to sumptuary legislation is important evidence of a growing consciousness of female marginalization, but also of the comforting and compensatory value of appearances. The paradoxical poly-functionality of female dress and its symbolic power is that, depending on the norms in place in a given city, it may indicate either privilege or marginalization. This shows the ambiguous significance that was attributed to female appearances.